Spread of Civilization Centers to Three Continents and Domination of Central Religion (Arab) Civilizations - Nadila, Tika; Laela, Yara (UAS PRESS, 2025)
The story of Noah is a long series of preaching journeys and the series of events in it provide valuable lessons for Muslims. Because Noah's long life history holds a very valuable historical treasury. Noah is called the father of world civilization because he continued the birth of humans on earth through his three children. This research is library research which examines the historical development of the spread of humans through Noah's son using a deductive approach. It was found that Noah's three sons were the fathers of the nations on the three continents, such as Sam, the father of the Semitic nation (Arab and surrounding areas), Yafis, the father of the Asian and European nations, and then Ham, who was the father of the African nation, they intermarried with each other, which then resulted in diverse ethnicities. The three heavenly religions known today are theological developments brought by the descendants of Sam bin Noah. Many civilizations were created by the descendants of Noah, such as the first kingdom built by Menes or Mishram, the descendants of Ham in Africa.